2012
DOI: 10.1021/ie2025739
|View full text |Cite
|
Sign up to set email alerts
|

Dilute Acid Hydrolysis of Sugar Cane Bagasse at High Temperatures: A Kinetic Study of Cellulose Saccharification and Glucose Decomposition. Part I: Sulfuric Acid as the Catalyst

Abstract: The kinetics of sugar cane bagasse cellulose saccharification and the decomposition of glucose under extremely low acid (ELA) conditions, (0.07%), 0.14%, and 0.28% H 2 SO 4 , and at high temperatures were investigated using batch reactors. The first-order rate constants were obtained by weight loss, remaining glucose, and fitting glucose concentration profiles determined with HPLC using the Saeman model. The maximum glucose yields reached 67.6% (200°C, 0.07% H 2 SO 4 , 30 min), 69.8% (210°C, 0.14% H 2 SO 4 , 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 37 publications
5
78
0
Order By: Relevance
“…Besides, for solubilizing purified raw cellulose from sugar cane bagasse [27], at temperatures above the proposed in this study, a higher decomposition of glucose at short periods of time was observed with the consequent lower concentration of fermentable glucose. Therefore, the operational conditions selected for further studies with residual cellulose film hydrolyzates were temperature, 130°C; reaction time, 2 h, and acid concentration, 6 %.…”
Section: Acid Hydrolysis and Steepest Ascentmentioning
confidence: 53%
“…Besides, for solubilizing purified raw cellulose from sugar cane bagasse [27], at temperatures above the proposed in this study, a higher decomposition of glucose at short periods of time was observed with the consequent lower concentration of fermentable glucose. Therefore, the operational conditions selected for further studies with residual cellulose film hydrolyzates were temperature, 130°C; reaction time, 2 h, and acid concentration, 6 %.…”
Section: Acid Hydrolysis and Steepest Ascentmentioning
confidence: 53%
“…Degradation of glucose due to the hydrolysis reaction produces compounds such as 5-hydroxymethyl furfural (5-HMF) and organic acids that have 5-HMF as a precursor, such as levulinic and formic acid [23].…”
Section: Hydrolysis Yieldmentioning
confidence: 99%
“…Dilute acid solutions are especially useful when lignocellulosic biomass has a significant proportion of hemicellulose because the hemicellulosic fraction is more easily hydrolyzed than cellulose [22]. The hydrolysis process with dilute acid solutions facilitates the neutralization process but has a lower yield of glucose from cellulose [23]. Concentrated acid solutions require lower processing temperatures and pressures, and the hydrolysis reaction occurs at a lower process time [22].…”
Section: Introductionmentioning
confidence: 99%
“…Acid and enzyme are among the most common catalysts for hydrolyzing cellulose into glucose [10,11]. In recent years, recyclable solid acids for cellulose hydrolysis have attracted great attentions [12][13][14][15][16][17][18][19][20][21]. However, achieving high selectivity and activity still remains a challenging task.…”
Section: Introductionmentioning
confidence: 99%